“A ARTE DE PRODUZIR EFEITO SEM CAUSA” (‘THE ART OF PRODUCE UNCAUSED EFFECT’): THE POSSIBILITIES OF READING THE ROMANCE OF LOURENÇO MUTARELLI - Marcos Antônio Fernandes dos Santos (2022)
The aim of this article was to identify the possibilities of reading the novel “The art of produce uncaused effect” (2008), by Lourenço Mutarelli, as well as the feelings and sensations triggered by the work before the act of reading. The methodology used was bibliographic in nature, and among the theorists who supported the discussions, there are: Iser (1996), Schollhammer, (2011), Blanchot (1997), Loytard (1993), among others. Far from solving the problems proposed by the work, the reader of the novel finds more doubts than answers. Fear of anguish are the main sensations resulting from reading. The reading itself concretizes the cathartic effect of the text, because the reader feels distressed by the experience of the Junior character and the impossibility of following a concrete path throughout the novel. The certainty is that there is no solution formulated either by the text, much less by the reader.